ORGANIZING THE ASSESSMENT AND MANAGEMENT OF FUND RISKS - Reimova Aynura Qoshqarbaevna (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
fund risk assessment and management play a critical role in ensuring financial stability and protecting investments. This article explores the identification, evaluation, and strategic management of risks associated with funds. The emphasis is placed on modern technological solutions, compliance with international standards, and tailored approaches to risk mitigation. Recommendations for improving fund risk management practices are also discussed.